2021
DOI: 10.1177/1932202x211057424
|View full text |Cite
|
Sign up to set email alerts
|

The Achievement Motivation Enhancement Curriculum: Evaluating an Affective Intervention For Gifted Students

Abstract: The present qualitative pilot study aimed to evaluate students’ perceptions of procedures and outcomes from an affective intervention to increase achievement motivation among gifted students. The intervention was implemented at a summer program with 20 students. Using inductive analysis, participants’ perceptions of the intervention and its effects were evaluated. This study’s findings show most students enjoyed the Achievement Motivation Enhancement sessions and felt they benefited from talking about their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…Our quantitative results showed that students reported improved positive academic self-perceptions, planning, and self-monitoring, all of which are directly targeted in the AME curriculum. These findings confirm what we found in previous research on the AME curriculum, both face-to-face (Desmet & Pereira, 2022) and online (Desmet et al, 2022). Contrary to our expectations, students did not report statistically significant improvements in goal valuation or mastery goal orientation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our quantitative results showed that students reported improved positive academic self-perceptions, planning, and self-monitoring, all of which are directly targeted in the AME curriculum. These findings confirm what we found in previous research on the AME curriculum, both face-to-face (Desmet & Pereira, 2022) and online (Desmet et al, 2022). Contrary to our expectations, students did not report statistically significant improvements in goal valuation or mastery goal orientation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is likely that the session needs to be revised to improve its effectiveness. Although another study has shown that the session resulted in significant changes for older students (Desmet et al, 2022), there is existing evidence that the session may not work well for middle school students (Desmet & Pereira, 2023). Thus, we hypothesize that the lack of significant change is likely due to the nature of the session and not due to the online delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned results are reinforced by Desmet and Pereira (2021), who report that the majority of students liked the Achievement Motivation Enhancement sessions and believed they benefitted from discussing their experiences in small groups. Students acknowledged enhanced self-perceptions and cited learning goal evaluation, goal formulation, and self-regulation skills as beneficial (Mammadov et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 95%